Mestari–kisälli-mallin soveltuvuus fennistiikan historiaan: Tapaustutkimuksena Sanakirjasäätiön alkuvaiheet [Applications of the master–apprentice model in the history of fennistics. Case study: the early years of the Sanakirjasäätiö...] - Onikki-Rantajääskö, Tiina (Virittäjä, 2011)
Artikkeli käsittelee sukupolvidynaamisen tarkastelun soveltuvuutta fennistiikan tieteenhistoriaan. Lähtökohtana on Karl Mannheimin sukupolvinäkemys Matti Virtasen (2001) soveltamassa muodossa. Tapaustutkimuksena on Sanakirjasäätiön ensimmäiset johtajanvalinnat (ajanjaksolla 1924−1934) Kustaa Vilkunan (1976) esittämien aikalaismuistelmien pohjalta. Sovellettu sukupolvinäkemys korostaa resurssien jakoa, ja artikkeli osoittaa, kuinka Sanakirjasäätiön varhaisilla linjauksilla on ollut nykyhetkeen ulottuvat vaikutukset fennistiikan resurssienjaossa. Sanakirjasäätiön jatkajan Kotimaisten kielten tutkimuskeskuksen (Kotuksen) resurssit ovat uudelleenarvioinnin kohteena, ja eduskunnassa on joulukuussa 2011 hyväksytty laki Kotimaisten kielten keskuksesta. Kirjoittaja pohtii, voiko Suomen vuoden 1918 sisällissodan nähdä Virtasen esittämällä tavalla sukupolvensa avainkokemuksena, jonka laukaisemaa ristiriitaa ratkottiin myöhemmässä toiminnassa. Fennomanian perinteen jatkajille vuoden 1918 trauma oli kansa-käsitteen jakautuminen. Sanakirjasäätiön alkuaikojen toimijoilla oli yhteiskunnallisia kytköksiä, jotka Vilkunan mukaan vaikuttivat johtajanvalintaan. Abstraktimmalla tasolla voidaan ajatella, että kyse oli fennomanian perinteen jatkajien erilaisista fraktioista, ideologisista suuntauksista. Keskiseksi muodostui jännite vanhemman jääkäriaktivistipolven edustajan Toivo Kaukorannan ja nuorempaan sukupolveen, Akateemisen Karjala-Seuran (AKS:n) fraktioon kuuluneen Lauri Hakulisen välillä. Virtanen korostaa mallissaan uuden suunnan ideologeina esiintyvien, hiukan vanhempien mestareiden ja heitä seuraavien kisällien suhdetta. Sanakirjasäätiön valinnoissa Kaukorannan taustalla vaikutti mestarina fennistiikan grand old man E. N. Setälä. AKS:n fraktiota johti ideologisesti opiskelija-aktivisti Niilo Kärki. Artikkelissa osoitetaan Martti Haavion (1972) muistelmien avulla, että suuntauksen keskeisiä ajatuksia olivat heimoaate ja pyrkimys kansalliseen eheyttämiseen, sisällissodan aiheuttaman kahtiajaon ylittämiseen sosiaalisten uudistusten ja nk. aitosuomalaisuuden avulla, johon kuului myös pyrkimys Helsingin yliopiston suomenkielistämiseen. AKS:n sisäiset ideologiset erimielisyydet johtivat siihen, että maltilliset kärkiläiset erosivat AKS:stä. Monista entisistä AKS-läisistä tuli professoreita, yhteiskunnallisista vaikuttajista keskeinen oli myöhempi tasavallan presidentti Urho Kekkonen. Kysymys tieteensisäisistä vaikutteista on ongelmallisempi. Artikkelissa tarkastellaan sitä, kuinka murresanakirjan keruu laajeni Kaukorannan aloitteesta tavalla, jonka vaikutukset heijastuvat siihen, että sanakirjan kirjoittaminen on edelleen kesken. Suppeampaa toteutusta kannattanut Hakulinen näyttää yllättävänkin helposti mukautuneen hankkeen laajentamiseen. Fraktioristiriita päättyi toiminnan sisältöjen osalta sopuun, vaikka Kaukoranta joutuikin sittemmin eroamaan taloussotkujen vuoksi. Kirjoittaja tarkastelee suomen murteiden sanakirjahanketta osana kansallista projektia ja nostaa esiin kysymyksen, voiko murresanakirjan nähdä myös osana eheyttävää suuntausta. Kansallisten tieteiden toimijoiden verkostoitumista tarkasteltaessa vaikuttavaksi tekijäksi paljastuu myös koulutausta: Hakulinen ja Haavio olivat luokkatovereita Turun klassisessa lyseossa. Laajemmin esiin nousee kysymys koulun ja kansanvalistuksen merkityksestä kansallisessa projektissa sekä murretietoja Sanastaja-lehden kyselyihin lähettäneiden maallikkovastaajien rooli malliesimerkkinä varhaisesta talkoistamisesta (crowdsourcing) ja nationalismin ulottuvuuksista, joissa risteää ylhäältä alaspäin suuntautuva kansallinen projekti ja alhaalta nouseva kansan oma aktiivisuus. — Applications of the master–apprentice model in the history of fennistics. Case study: the early years of the Sanakirjasäätiö (the ‘Dictionary Foundation’) This article examines the applications of the theory of generations as regards the scientific history of fennistics. As its starting point, the article takes Karl Mannheim’s theory of the sociology of generations, as adapted and applied by Matti Virtanen (2001). The case study in question deals with the early board appointments of the Sanakirjasäätiö (the ‘Dictionary Foundation’) during the period 1924–1934, based on contemporary notes by Kustaa Vilkuna (1976). The adapted theory of generations stresses the division of resources, and the article demonstrates that policy decisions made in the early years of the Dictionary Foundation’s existence continue to have an impact on the division of resources within the field of fennistics to this day. Funding provision for the Research Institute for the Languages of Finland, which has latterly assumed the mantle of the former Dictionary Foundation, are currently being reassessed and in December 2011 a bill was passed in parliament redefining the role of the Institute. The writer explores the question of whether, as Virtanen posits, the Finnish Civil War of 1918 can be seen as the key, defining event of a generation and one whose conflicts were left to be resolved in subsequent action. For those carrying on the traditions of Fennomania, the central trauma of the events of 1918 was the splintering of the idea of the ‘nation’. Key figures involved in the early years of the Dictionary Foundation had societal links that, in Vilkuna’s view, had a direct impact on the selection of board director. On a more abstract level, we may assume that this was a matter of different fractions and ideological strands within those carrying on the tradition of Fennomania. Notably, the tensions between the older generation of Jäger activists, represented by Toivo Kaukoranta, and the younger generation, represented by Lauri Hakulinen, a member of the AKS, the Academic Karelia Society, gradually assumed particular significance. In his model, Virtanen stresses the importance of the relationship between those different ideologies represented by slightly older masters and the apprentices that followed them. At the Dictionary Foundation, the selection of Kaukoranta was down in part to the influence of the grand old man of fennistics, E. N. Setälä. Fractions within the Academic Karelia Society were led, at least on an ideological level, by student activist Niilo Kärki. With the help of notes written by Martti Haavio (1972), the article contends that central to this strand of thought were the notion of Finnish ‘people’ and a desire to foster national unity and to overcome the divisions brought about by the Civil War through the implementation of a variety of social reforms and what came to be known as the idea of aitosuomalaisuus, that which is ‘truly’ Finnish, which included a desire to make the University of Helsinki entirely Finnish speaking. Internal ideological divisions within the Academic Karelia Society resulted in the resignation of many of the more moderate Kärki followers. Many former AKS members went on to become professors, while the most significant former member of the group was one Urho Kekkonen, who later became President of Finland. The question of influences from within academia is rather more problematic. The article explores the ways in which the gathering of materials for the dialect dictionary was greatly expanded through one of Kaukoranta’s initiatives – the effects of which mean that the dictionary is still incomplete. Hakulinen, who had originally argued for a more concise approach, seems to have acquiesced to the expansion of the project with surprising ease. The fractious conflict was resolved, at least with regard to the content of the Foundation’s policies, though Kaukoranta was later forced to resign because of the financial irregularities at the Foundation. The writer examines the dialect-dictionary project as part of the national project and considers whether it can also be seen as part of the ideology of a unified Finland. In an examination of the networks of the most prominent figures of the human sciences, it would appear that education is a key factor: Hakulinen and Haavio were classmates at the classical school in Turku. In a wider context another question arises, namely that of the significance within the national project of school and public education, the role of lay respondents who answered questionnaires on the subject of dialects for the Sanastaja magazine as an early example of so-called ‘crowd-sourcing’, and the dimensions of nationalism featuring, on the one hand, the national project moving from the upper echelons of society downwards, and, on the other, action rising from within the ranks of the people themselves.